IMPROVING ARCHITECTURE STUDENTS’ ENGLISH VOCABULARY THROUGH THE USE OF ARCHITECTURAL DRAWINGS - Fidyati Fidyati (Universitas Islam Negeri Banda Aceh, 2018)
This study aims to find out the effectiveness of architectural drawings in teaching English vocabulary at first-semester college students of Architecture, Malikussaleh University, Lhokseumawe, Aceh, Indonesia. The media applied in the research worked in both improving Architecture-major students’ ability to learn the target language and motivating them in the teaching-learning process. A likert questionnaires analysis was used to determine factors affecting students’ lack of English vocabulary. The quasi-experimental method was applied to acquire the test data needed. The t-test formula was then used to find out the differences between conventional teaching technique and using-architectural-drawings technique through the pre-test and post-test scores. Based on the analysis, the findings showed that there was a significant success on improving the students’ vocabulary mastery. However, as the architectural drawings used in the research were limited on the presentation type of drawing, other kinds of architectural drawings may not result in the similar way.